Litigation and Inequality : Federal Diversity Jurisdiction in Industrial America, 1870-1958. - Purcell, Edward A. (Oxford University Press, 1992)
Explores the relationship between legal and social change through a study of American litigation practice. The text examines changing litigation patterns in suits between individuals and corporations over tort claims for personal injuries and contract claims for insurance benefits.